The value of glycated hemoglobin as predictor of organ dysfunction in patients with sepsis - Lee, Young Seok (PLoS One, 2019)
BACKGROUND: In patients with sepsis, an inflammatory response can lead to destruction of the glycocalyx. These alterations cause the progression of organ dysfunction. Destruction of the glycocalyx can also occur in chronic hyperglycemia. Glycated hemoglobin (HbA1c) is a reliable marker of premorbid hyperglycemia. We investigated the association between HbA1c level at admission and the degree of organ dysfunction progression 72 hours after admission and ICU mortality. METHODS AND FINDINGS: This study was a retrospective observational study. Logistic regression and correlation analyses were performed to evaluate the association between the HbA1c level and the degree of organ dysfunction progression 72 hours after ICU admission. We applied survival analysis to examine the association between HbA1c level and ICU mortality. A total of 90 patients were included in this study. The association between HbA1c level and degree of organ dysfunction progression was significant (r = 0.320; P = 0.002). Multivariable logistic regression analysis showed that high HbA1c level (≥6.5%) (OR, 2.98; 95% CI, 1.033–8.567; P = 0.043) were significant, independent predictors of severe organ dysfunction progression. Patients with an HbA1c level ≥6.5% exhibited significantly greater liver and kidney dysfunction progression 72 hours after ICU admission compared with those with an HbA1c level <6.5%. Kaplan-Meier analysis showed that the survival period was significantly shorter in patients with an HbA1c level ≥6.5% than in those with an HbA1c level <6.5% (P < 0.001). Multivariable Cox proportional hazard analysis showed that HbA1c level ≥6.5% (HR, 3.49; 95% CI, 1.802–6.760; P <0.001) were significant, independent predictors of ICU mortality. CONCLUSIONS: In patients with sepsis, the HbA1c level at ICU admission is associated with progression of organ dysfunction 72 hours later and with ICU mortality. It may be important to assess HbA1c level at ICU admission because it may be a predictor of ICU outcome. For patients with a high HbA1c level (≥6.5%), greater attention should be paid to the possibility of organ dysfunction progression.